The Impact of the Financial Fund on the Efficiency of Waste Electrical and Electronic Products Processing in China. Issue 1 (August 2020) - Chen, Shuai; Yang, Jiameng; Gao, Qianhui; Xing, Yingxue
Abstract: With the support of the fund, the recovery and dismantling volume of WEEE in China have been greatly improved, but it is far away from the provisions of the long term planning for the construction of renewable resources recovery system. In the paper, the development of waste electrical and electronic products processing field is analyzed, from which we find the shortcomings of the existing electronic waste fund operation in China. First of all, the paper analyzes the influence of household appliances dismantling fund on household appliances production industry by using partial equilibrium model, and finds that expropriation fund is not the main reason for enterprises to adjust their production and operation strategies and adopt ecological design. Through further analysis, it finds that the main reason for enterprises to adopt ecological design is firstly attributed to the public's increasing attention to health, and secondly to the environmental standards and sections issued by the government subsidy and other policies directly related to ecological design. In terms of the fund subsidies, DEA model is used to analyze the impact of fund subsidies on the dismantling and treatment industry. The model results show that fund subsidies are effective for the dismantling and treatment of 5 major electronic waste products. On one hand, they alleviate the loss of enterprises; on the other hand, they promote energy conservation and emission reduction, and improve the efficiency of dismantling. The economic benefit, environmental and resource benefit and social benefit of the fund of dismantling and processing enterprises are all affected by the fund subsidy. Finally, it gives policy implications. In order to improve the financial efficiency of the fund, it is suggested that in the aspect of fund policy management, we should appropriately improve the current fund collection standards, adjust the products and scope of the fund collection catalogue, and formulate differentiated collection standards for the products with different environmental protection performance, so as to realize the incentive and constraint of the fund collection on the production enterprises. In terms of the fund subsidy, we should further adjust the design of subsidy amount, establish a long-term subsidy performance evaluation system and a qualification examination mechanism for enterprises entering and exiting the subsidy list, ensure the effectiveness of fund subsidy distribution, narrow the gap in the fund pool, reduce the waste of fund subsidy, and achieve the unity of economic benefits, resources and environmental benefits and social benefits.